2019
DOI: 10.1200/jco.19.01608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Unconscious Bias: Speaker Introductions at an International Oncology Conference

Abstract: PURPOSE In a professional setting, the introduction of female speakers without their professional title may have an impact on the public’s perception of the female speaker. We examined how professional titles were used during speakers’ introductions at the ASCO Annual Meeting. METHODS We conducted a retrospective, observational study of video-archived speaker introductions at the 2017 and 2018 ASCO Annual Meetings. A “professional address” was defined as the professional title followed by the speaker’s full na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 28 publications
0
29
1
Order By: Relevance
“…In a review of presentations from the inaugural ACG 2020 Virtual Annual Meeting, we found no gender differences in the formality of speaker introductions or speaker self-introductions. This is in contrast to previously published work documenting gender-based difference in the use of professional titles in the introductions of speakers at in-person internal medicine and oncology conferences [ 11 , 12 ]. The first article to formally evaluate speaker introductions at professional meetings in medicine was a retrospective observational study of video-archived speaker introductions at Internal Medicine Grand Rounds at two locations of an academic medical center.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…In a review of presentations from the inaugural ACG 2020 Virtual Annual Meeting, we found no gender differences in the formality of speaker introductions or speaker self-introductions. This is in contrast to previously published work documenting gender-based difference in the use of professional titles in the introductions of speakers at in-person internal medicine and oncology conferences [ 11 , 12 ]. The first article to formally evaluate speaker introductions at professional meetings in medicine was a retrospective observational study of video-archived speaker introductions at Internal Medicine Grand Rounds at two locations of an academic medical center.…”
Section: Discussioncontrasting
confidence: 93%
“…The findings published in 2017 highlighted that women were less likely to be addressed by professional title than men, and that this difference was driven by men introducing women speakers informally. Follow-up studies examining introductions at the 2017 and 2018 American Society of Clinical Oncology (ASCO) Annual Meetings and the American Academy of Dermatology 2019 annual meeting replicated these findings [ 12 , 13 ]. These important studies demonstrated the persistence of gender-based disparities in professional introductions across multiple medical disciplines and professional settings.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent studies have documented how these challenges play out within the field of oncology specifically. Duma and colleagues 8 documented that women speaking at a prominent national oncology meeting were less likely to be introduced by professional titles. Knoll and colleagues 9 documented that women attend fewer national conferences despite being equally convinced of the important benefits of attendance, and the biggest reported obstacle to attendance was related to childcare.…”
mentioning
confidence: 99%